1996
DOI: 10.1002/(sici)1097-0045(199603)28:3<195::aid-pros6>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral prostatectomy: Mortality and morbidity

Abstract: In 1989 two large‐scale multicenter studies on the mortality and morbidity of transurethral resection of the prostate were published [Mebust et al.: J Urol 141:243–247, 1989; Roos et al.: N Engl J Med 320:1120–1124, 1989]. These studies caused us to perform a retrospective study on a total of 1,211 consecutive patients who underwent transurethral resection of the prostate at our department between January 1988 and July 1991. The mortality rate in the 1,211 patients subjected to transurethral resection of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 0 publications
2
37
0
5
Order By: Relevance
“…However, the procedure has complications, such as blood loss, that need blood transfusion (up to 8%) and transurethral resection (TUR) syndrome (up to 2%) 6. The sharp cutting action using plasmakinetic electrovaporization and resection using a loop electrode (as in the Gyrus system) should prevent these complications, improving homeostasis during the procedure and reducing the risk of hyponatremia (normal saline instead of glycine was used as the irrigation fluid) 61013. The bipolar electrosurgical equipment simultaneously vaporizes tissue during resection, which controls bleeding as it effectively and accurately seals all bleeding points 8101415.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the procedure has complications, such as blood loss, that need blood transfusion (up to 8%) and transurethral resection (TUR) syndrome (up to 2%) 6. The sharp cutting action using plasmakinetic electrovaporization and resection using a loop electrode (as in the Gyrus system) should prevent these complications, improving homeostasis during the procedure and reducing the risk of hyponatremia (normal saline instead of glycine was used as the irrigation fluid) 61013. The bipolar electrosurgical equipment simultaneously vaporizes tissue during resection, which controls bleeding as it effectively and accurately seals all bleeding points 8101415.…”
Section: Discussionmentioning
confidence: 99%
“…The sharp cutting action using plasmakinetic electrovaporization and resection using a loop electrode (as in the Gyrus system) should prevent these complications, improving homeostasis during the procedure and reducing the risk of hyponatremia (normal saline instead of glycine was used as the irrigation fluid) 61013. The bipolar electrosurgical equipment simultaneously vaporizes tissue during resection, which controls bleeding as it effectively and accurately seals all bleeding points 8101415. The plasmakinetic system, however, uses a smaller loop compared with the conventional TURP, which requires more strokes for every unit volume of prostate resected 916–18.…”
Section: Discussionmentioning
confidence: 99%
“…The recently reported incidence is 0-0.25% in large studies [12]. Other authors reported a 30-day mortality incidence 0.2-0.8% [13].…”
Section: Discussionmentioning
confidence: 93%
“…Tiene una tasa de mortalidad entre 0,2-1,5% y una morbilidad en conjunto del 11,1% 25,26 con un porcentaje de reintervención del 6-13% 27 .…”
Section: ¿Sigue Siendo La Rtu Prostática Elunclassified